Perancangan Visual Festival Kapal Hias Nelayan Sungsang Dalam Upaya Pelestarian Budaya - Dewanto, Yahya; Ali, Ferdiansyah; Anzura Sahri, Moreira (Magenta | Official Journal STMK Trisakti, 2023)
Sungsang Village is located in the Muara Sungai Musi, South Sumatra, and has only been designated as a tourist village in 2020. For this reason, building the image of a city/village is one of the most important efforts to introduce a new tourism village. One of the efforts of the government is to hold the Breech Fisherman Ornamental Boat Festival in 2020, in addition to improving the image, this event is also held to move the economic wheels of the community in the west wind season. Unfortunately, This event does not have a consistent and professional Ship Visual Design. Futhermore, the authors designed the Visual Festival of Breech Fisherman Ornamental Boats using a descriptive and quantitative approach, namely by directly interviewing related parties. As a result, this Ï”inal project uses the Graphic Standard Manual (GSM) which will be applied to supporting media properly and consistently, in accordance with the vision and mission of the Breech Fisherman Ornamental Boat Festival event. The concept created is â€œSemarak Ombakâ€ based on the concept of mind mapping.